Hellenic Integrative Psychotherapy: A Total Holistic Approach - Nestoros, Joannis N. (Scientific Research Publishing, 2018)
An integrative psychotherapy model is described which proposes that the basic “schools” of psychotherapy, that is the psychodynamic, behavioral, humanistic/ existential, systemic and biological approaches can be synthesized into a new improved paradigm. This total holistic approach is not in conflict with any of the contributing models which are perceived as complementary to each other. Moreover, there is ample scientific evidence that all traditional psychotherapies share the same common therapeutic factors. Hellenic integrative psychotherapy comprises a new idealistic approach which has different improved properties in the same way that Water differs from its constituents Oxygen and Hydrogen. Elements of ancient Greek philosophy, mythology, history, literature, ethics, values, reasoning, mentality and way of life are considered to be an important constituent of Hellenic Integrative Psychotherapy. Hippocratic diet, Bodily exercises that enhance physical wellness and brain function, Therapeutic thermal and cold baths, Thalassotherapy, Exposure to sunlight, Music therapy, Theater therapy, Art therapy, Therapeutic architecture and the exposure to a Therapeutically beautiful physical environment constitute important integral elements of the presented total holistic approach. Last but not least, Neurofeedback (training of the EEG) and Event Related Potentials (ERPs) will be employed.
Keywords: Therapeutic Physical Environment; Therapeutic Architecture; Therapeutic Greek Philosophy and Culture; Neurofeedback